Pelatihan Pembuatan Pupuk Tanaman Hias Dengan Bahan Baku Sekam Padi Basah Lokasi Di Kelurahan Pringgokusuman - Suyanto Muhammad; Prastyono Eko Pambudi; subandi (Fakultas Sains Terapan, 2023)
A clean environment is the dream of all Jogjakarta people. Cleanliness and beauty of the City is one of the New Programs launched by the City Government of Jogjakarta, so on this occasion we are trying to enter the RW. 03 and RW.24 Pringgokusuman Village. To help the Clean Environment Program and Activities to make compost from Rice Husk, where this activity will help reforest the Farmers' Self-Help Groups in urban areas. The target is community service, so that people can understand the importance of a clean and healthy environment, besides that the community can know how to properly care for and manage homemade fertilizer from rice husks. Implementation of this community service activity, in collaboration with IST AKPRIND. Community service activities are social activities by providing training to the community regarding the care of ornamental plants around the house by utilizing compost from rice husks by mixing or stirring them together with other ingredients. From the rice milling process, about 20-30% husk is usually obtained, bran is between 8-12% and milled rice is between 50-63% of the initial grain weight data. Husk with a high percentage can cause environmental problems. In terms of data, the chemical composition of the husk contains several important chemical elements, including moisture content: 9.02%, crude protein: 3.03%, fat: 1.18%, crude fiber: 35.68%, ash: 17.17%, Basic carbohydrates: 33.71. The chemical composition of rice husk according to DTC-IPB, Carbon (Charcoal): 1.33%, Hydrogen: 1.54%. Obviously. Keywords: Rice Husk, Ornamental Plants, Compost, Clean environment.